Imagem do contador a partir do perfil esperado do egresso em ciências contábeis pelas instituições de ensino superior e de publicações selecionadas na rede social instagram - Caetano, Julio Cezar Mendes (2024)
This study investigated how the stereotypes of accounting professionals, present in institutional and humorous publications on the social network Instagram, reflect the profile of graduates expected by the accounting courses at Brazilian Higher Education Institutions (HEIs). To achieve this objective, a qualitative approach was adopted, in which the stereotypes were extracted and analyzed interpretatively, based on the Theory of Social Representations. The methodology was based on the stereotype analysis model proposed by Albu et al. (2011), which included the definition of a list of stereotypes, data collection from the descriptions of the accounting courses of the twenty main HEIs in Brazil, according to the 2023 Folha University Ranking (RUF), and publications on Instagram, both from institutional pages and humor pages. The analysis revealed a dichotomy between the idealized image of the accountant, promoted by HEIs and institutional pages on Instagram, and the negative stereotypes found on humor pages on the same social network. HEIs portray the accountant as an ethical, competent, and strategic professional, essential for economic and social development, while memes satirize the accountant as a tedious, bureaucratic individual, detached from social reality. This divergence between social representations can generate negative impacts on the profession, such as the demotivation of students and the devaluation of accounting work. Moreover, the prevalence of negative stereotypes can lead to an illusory correlation, associating the accountant with negative events, such as fraud, even though these are rare. The study highlights the importance of constructive dialogue between HEIs, professional bodies, and professionals to promote a more accurate and positive image of accounting. Actions such as curriculum review, communication campaigns, and the development of interpersonal skills can contribute to the construction of a more solid and valued professional identity. Despite limitations, such as the focus on a specific set of data sources and the predominantly qualitative approach, this study offers an important analysis of the social representations of the accountant and their implications for the profession, fostering future investigations into the underlying causes of stereotypes and the development of effective strategies to promote a positive image of accounting.